The Influence of Fermentation-Control on the Colloidal Stability and the Reducing Power of the Resulting Bottom Fermented Beers - Pöschl, Moritz; Bauer, Simon; Leal, Louis; Illing, Susan; Stretz, Dominique; Wellhoener, Urs; Tenge, Christoph; Geiger, Eberhard (BrewingScience, 2007)
The focal point of this work was to evaluate variations in fermentation-control, which included different fermentation temperatures and different pitching rates, the usage of yeast from various numbers of generations as well as the application of pressure fermentation. Of particular interest was the monitoring of haze relevant polyphenols and proteins as well as the detection of antioxidative capacity, which was differentiated between fast reducing substances and total reducing power. The force tests showed reproducible lower formation of colloidal haze in the beers resulting from fermentation at lower temperatures and from decreasing numbers of yeast generations. Also lower pitching rates and pressure fermentation seem to improve colloidal stability. The best reducing power, which does not influence colloidal stability in either case, resulted from cold fermentation and higher pitching rates. It has been shown that variations in the field of fermentation performance may have an impact on the colloidal stability. Thus optimising the fermentation performance and pitching technology can be regarded as one further step to improve colloidal stability in a technological way.